Interpretasi Kata Fasād dan Dampak Terhadap Kerusakan Lingkungan - Iffa Nurul Azza Farida Farida; Abdul Fatah; Althaf Husein Muzakky (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This article examines the meaning of the word fasād in the Qur'an and its relation to environmental damage. The purpose of this study is to explain how the concept of fasād can be used to understand human behavior that causes damage to nature, as explained in Surah Ar-Rūm verse 41. The results of the study show that fasād encompasses all forms of actions that cause imbalance and damage to the earth, whether physically, morally, or socially. The Qur'an emphasizes that humans should not destroy the earth after Allah has repaired it, because environmental damage arises from human greed and negligence in carrying out their duties as caliphs. Therefore, the values in the Qur'an can be used as a moral and spiritual foundation for protecting and preserving the environment in a sustainable manner.